Speck, Jeff (2012). Walkable City: How Downtown Can Save America, One Step at a Time - Marquet, Oriol (Documents d'Anàlisi Geogràfica, 2015)
Speck, Jeff (2012) Walkable City: How Downtown Can Save America, One Step at a Time Nueva York: North Point Press, 312 p. ISBN 978-0865477728